2018
DOI: 10.1002/jcb.26630
|View full text |Cite
|
Sign up to set email alerts
|

ORP150‐CHIP chaperone antagonism control BACE1‐mediated amyloid processing

Abstract: BACE1, a key protein involved in Alzheimer's progression, initiates Aβ42 generation that induce senile plaques in brain. However, the role of chaperone synergy or antagonism on BACE1-mediated amyloid processing is unknown. We have discovered that BACE1 as well as Aβ42 are antagonistically controlled by ER chaperone ORP150 and cellular chaperone CHIP. We have shown ORP150 as a chaperone interacts with and stabilizes BACE1 at post-translational level. Furthermore, ORP150 enhances BACE1-mediated amyloid processin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…36 HYOU1 can protect neurons from cell death and plays an important role in neurodegenerative diseases. 25,[37][38][39] HYOU1 can protect cardiomyocytes and vascular cells from apoptosis, and plays an important role in improving atherosclerosis and regulating cardiac ischemia/reperfusion.…”
Section: Structure and Function Of Hyou1mentioning
confidence: 99%
See 2 more Smart Citations
“…36 HYOU1 can protect neurons from cell death and plays an important role in neurodegenerative diseases. 25,[37][38][39] HYOU1 can protect cardiomyocytes and vascular cells from apoptosis, and plays an important role in improving atherosclerosis and regulating cardiac ischemia/reperfusion.…”
Section: Structure and Function Of Hyou1mentioning
confidence: 99%
“…HYOU1 signaling plays an essential role in neurodegenerative diseases. 25,[37][38][39] The common symptom of many neurodegenerative diseases is the accumulation of misfolded proteins in the lumen of nerve cells, especially Alzheimer's disease and Parkinson's disease. 62 The study found that in post-mortem brain tissues and cell culture models, upregulation of ER stress markers was observed in diseases such as Alzheimer's disease and Parkinson's disease.…”
Section: Role Of Hyou1 In Neurodegenerative Diseasesmentioning
confidence: 99%
See 1 more Smart Citation